(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study examines the cross-market efficiency of the Indian index options market by analyzing the Put-Call Parity (PCP) condition using spot index values and futures prices of Nifty50 index options traded on the National Stock Exchange (NSE) of India. Employing a comprehensive dataset spanning 1 April 2018 to 31 March 2024 this study investigates potential arbitrage opportunities while considering the impact of transaction costs and market frictions. The findings reveal that a significant number of PCP violations occur in both spot-based and futures-based markets. However, the inclusion of transaction costs substantially reduces exploitable arbitrage opportunities, particularly for retail investors. The violations are primarily concentrated in put options with short maturities and at-the-money strikes, which is attributed to their higher market liquidity. Although mispricing levels are more pronounced in options with longer maturities and far-from-the-money positions, the reduced liquidity in these contracts hinders the execution of profitable arbitrage strategies in the options market. The study concludes that, while theoretical arbitrage opportunities exist, real-world constraints, such as transaction costs and execution delays, largely render them unexploitable, resulting in a quasi-efficient market state for Indian index options. This study highlights the need for further investigations using high-frequency data, algorithmic trading, and the impact of regulatory changes and technological advancements on market efficiency in emerging economies.